Bisphosphonate-Related Osteonecrosis of the Jaw Around Dental Implants - Shirota, Tatsuo; Nakamura, Atsushi; Matsui, Yoshiro; Hatori, Masashi; Nakamura, Masanori; Shintani, Satoru (IntechOpen, 2011)
None